Effect of a cluster on gas-solid drag from lattice boltzmann simulations - Shah, Milinkumar; Utikar, Ranjeet; Tade, Moses; Evans, G.; Pareek, Vishnu (CSIRO, 2012)
Formation of particle clusters in fast fluidization of fine particles significantly affects the gas-solid drag force. Accounting for the effect of clusters in gas-solid drag is critical for accurate modelling of gas-solid flows. As a result several modifications to the empirical gas-solid drag models have been proposed. However, computational studies with these modified drag models have shown their limitations in capturing the inherent heterogeneity found in the gas-sold flow. Generally, this has been attributed to the lack of understanding on effects of cluster on the gas-solid drag force. In this study, direct numerical simulations using lattice Boltzmann method have been conducted to investigate the effect a single cluster and its properties such as cluster voidage and fraction on the gas-solid drag force over a wide range of overall voidages and particle Reynolds numbers. The numerical observations clearly show that particle configuration with a cluster exhibit a considerably lower drag than particles in random arrangement. Furthermore, major drag reduction is observed when the inter-particle distances within the cluster decreases for voidage ranging from maximum voidage to 0.7. The simulations show that for constant cluster voidage, minimum drag force occurred around 0.9to 0.95 overall voidage. The drag force increased steeply with decrease in the overall voidage. The findings reported here will pave the way to improved drag correlation that can be used in CFD simulations that solve the average two-fluid equations.